FLAVONOIDS FOR ANTI-HYPERURICEMIA: A LITERATURE REVIEW - Putri, Diah Pitaloka; Putra, Kusuma Wijaya Ridi (Nurse and Health: Jurnal Keperawatan, 2024)
Background: Hyperuricemia is a condition on the level of uric acid in the blood increases, it is more than 6.0 mg/dL in women and more than 7.0 mg/dL in men and is currently a public health problem because of its increasing prevalence. Hyperuricemia is believed to have contributed to an increased risk of mortality and morbidity associated with various diseases such as metabolic syndrome, kidney disease, cardiovascular disease, etc. Flavonoids in plants can be used to help treat hyperuricemia due to it is believed to have low side effects. Objective: The aim of this article was to review the effect of flavonoids on plants as anti-hyperuricemia. Design: The design used in preparing this manuscript is an integrative review by reviewing articles on the impact of flavonoids as anti-hyperuricemia. Data Sources: Sources of information were obtained from research articles from 2004-2023 which were accessed through PubMed, Scopus, Sciendirect, SpringerLink, and Google Scholar. Review Methods: In the process of selecting articles to ensure the quality of the articles used in preparing this article, the authors used the PRISMA method. Results: In this article, 15 in vivo studies related to the effect of plants containing flavonoids (kaemferol, luteolin, apigenin, rutin quercetin, morin, butein, vitexin, etc.) on reducing uric acid levels by various mechanisms from previous studies. Conclusion: Based on several studies reported that flavonoids have an effect on lowering uric acid levels by inhibiting xanthine oxidase (XO) activity, affecting the expression of uric acid transporters in the kidneys which contribute to the increase of excretion of uric acid in urine.